Manfaat Pemberian Imunisasi (Vaksin Measles Rubella) Pada Anak Di Taman Kanak Kanak Kota Makassar - Herlianty, Herlianty; Latif, Sarifudin Andi; Nurhaedah, Nurhaedah; Afrika, Eka; Fatany, Alief Ihram; Prihatini, Surya (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2024)
Rubella is included in mild diseases in children, but can have a bad impact if it occurs in pregnant women in the first trimester, namely miscarriage or defects in babies often called Congenital Rubella Syndrome (CRS) such as heart and eye abnormalities, deafness and developmental delays. The purpose of PkM in administering the Measles Rubella vaccine is to stimulate the formation of immunity or resistance to measles and rubella. The method used in PkM activities is the provision of immunization and health education about Measles Rubella in kindergarten children who are the primary targets of the community service program. The results of community service are an increase in knowledge and benefits of immunization (measles rubella vaccine) in children in kindergarten before and after. The conclusion of this activity is an increase in the coverage of Measles Rubella and Antibody in toddlers, especially Kindergartens in Gowa in administering immunization (measles rubella vaccine).